FRI0594 A case of mosaicism in TNF associated periodic syndrome (TRAPS). (15th June 2017) - Kontzias, A; Calabrese, C; Cheng, Y-W
Abstract : Background: Tumor necrosis factor receptor (TNFR)–associated periodic syndrome (TRAPS) is an autosomal-dominant disease caused by gain-of-function mutations in the TNFRSF1A gene, which encodes the 55-kd TNFR type I (TNFRI) protein. Mosaicism has been recently idenitfied in a single patient. 1 A 60 year old male presented with a 6 year history of intermittent fever as high as 103.5, lasting 3–4 weeks with associated peritoneal symptoms, arthralgias, myalgias, lymphadenopathy, bilateral episcleritis, erythematous rash in his torso. Prednisone up to 60 mg daily only partially alleviated his symptoms and colchicine was ineffective. Objectives: To explore the role of mosaicism in a patient with adult onset TRAPS phenotype. Methods: DNA was extracted from the patient's whole blood, saliva and hair root. The TNFRSF1A gene was analyzed by Sanger sequencing in all tissues, and next-generation sequencing in whole blood. In silico molecular modeling was performed to predict the structural and functional consequences of the tumor necrosis factor receptor (TNFR) type I protein mutation. Results: Sanger sequencing and next-generation sequencing methods revealed differential tissue presence of a misense mutation at c.265 T>C p.Phe89Leu (F89L) Chr12(GRCh37):g.6442960A>G ex3 rs104895245. The mutant allele was present in whole blood and buccal mucosa and absent in hair root, supporting the presence of somatic TNFRSF1A mosaicism. In silico prediction modeling with SIFT and PolyPhen2 suggested that this mutation led to numerous structural rearrangements which resulted in changes in the protein surface profile. The patient had a complete response to treatment with canakinumab an interleukin-1 beta blocker, with resolution of symptoms and normalization of acute-phase protein levels. Conclusions: This is the second reported case of TNFRSF1A mosaicism in a patient with TRAPS, which was attributable to a de novo mosaic missense mutation in the TNFRSF1A gene. (c.265 T>C) p.Phe89Leu (F89L) The clinical picture in this patient, including the complete response to IL-1 blockade, was typical of that found in TRAPS. This case suggests that adult onset TRAPS phenocopies may be attributed to somatic (or postzygotic) mutations. References: Rowczenio et al Association of Tumor Necrosis Factor Receptor–Associated Periodic Syndrome With Gonosomal Mosaicism of a Novel 24-Nucleotide TNFRSF1A Deletion ARTHRITIS & RHEUMATOLOGY, Vol. 68, No. 8, August 2016, pp 2044–2049. Disclosure of Interest: None declared